AB0923 Subclinical entheseal involvement in patients with psoriasis: A case-control ultrasound study. (23rd January 2014) - Nerviani, A.; Cerutti, C.; Molinari, R.; Deidda, S.; Sola, D.; Steffanini, M.; Bellan, M.; Pirisi, M.; Sainaghi, P.P.
Abstract : Background: Ultrasonography (US) can demonstrate early abnormalities in entheses of asymptomatic patients. The existence of pre-clinical entheseal involvement in patients with psoriasis is debated. Objectives: To verify by US the presence of subclinical enthesitis in psoriatic patients without clinical features of arthritis/enthesitis. Methods: We enrolled 47 consecutive patients with a definite diagnosis of psoriasis and 47 sex, age and BMI-matched control. We excluded psoriatic patients treated with systemic drugs or with psoriatic arthritis, with recent trauma or surgery, BMI>30 kg/m 2, diabetes, dyslipidemia or hyperuricemia. All patients underwent bilateral US scan of the following entheses: flexors and extensors insertion into omeral epicondyle and epitrochlea, quadriceps, proximal and distal patellar ligament, achilles tendon and plantar aponeurosis. Entheses were evaluated for structural (calcifications, enthesophytes and bone erosions) and morphological (increased entheseal thickness of tendon, bursitis, vascular signals Power Doppler) alterations. The Glasgow Ultrasound Enthesitis Scoring System (GUESS) was calculated. US was performed by a rheumatologist trained in musculoskeletal US. Non parametric and chi-square tests were used to compare variables among groups. Results: Patients and controls were similar for age, BMI and sex distribution (Mann-Whitney U test, p>0.05). Calcifications and enthesophytes were more frequent in psoriatic patients versus controls (55.3% vs 38.3%, χ2, p<0, 01). Thickness at the plantar aponeurosis insertion was significantly increased in psoriatic patients in comparison to controls (Mann-Withney U test, p<0.0002). There was a trend (not significant) for a higher GUESS score in psoriatic patients. Conclusions: In conclusion, abnormal entheseal US features are common in psoriatic patients without clinical enthesitis. Future studies are warranted to verify whether US surveillance may be useful to identify and treat early entheseal involvement in psoriasis, reducing disease burden. Disclosure of Interest: None Declared